Grain Storage Management in India - Sharon, M Esther Magdalene; Abirami, C V Kavitha; Alagusundaram , K (Journal of Postharvest Technology, 2024)
India’s grain production has steadily increased due to advances in technology, but post-harvest loss is constant at 10%. Losses during storage, accounts for around 6% of the total losses as proper storage facilities are not available. In India, food grains are stored using traditional structures by small farmers. The surplus grains are stored with government agencies like: Food Corporation of India (FCI), Central and State warehousing Corporations. The commonly used storage method is Cover and Plinth (CAP) storage, which is economical but loss of grains is inevitable. Very few scientific storage structures like silos are available with these agencies. The government is taking initiatives now in building silos for long-term safe storage of grains since we do not have enough storage capacity as of now. Drying of harvested grains to safe moisture levels will reduce losses to a greater extend. However, very less literature is available on behaviour of grains after harvest for Indian climatic conditions. Therefore, there is a need for research to develop management guidelines for safe storage and drying to ensure quality management of stored grains.